Apoyo psicológico y la depresión en los pacientes oncológicos del instituto del cáncer Solca Cuenca periodo 2020 - Guzmán Paredes, Evelyn Cristina (2021)
The psychological support before the diagnosis and treatment of cancer, allows to reduce the conflicts that it triggers, in its different areas (physical-emotional-social), depression is the mental health disease that most affects cancer patients, the same that causes serious problems in physical and mental health, interfering with the efficiency of treatment against this disease. The present research work entitled: Psychological support and depression in cancer patients of the Solca Cuenca Cancer Institute period 2020; Its general objective is: To know how psychological support helps depressive cancer patients. The research design presents a mixed qualitative and quantitative approach, non-experimental of a descriptive nature, in which the scientific, analytical-synthetic methods were used; The IDERE test was used in the first instance to determine the sample in a timely manner, continuously a sociodemographic data collection form, the BDI II test to determine the level of depression of the patients, it was finally analyzed in the Excel 2016 program. Reported frequencies and percentages. In the results of the research, it is concluded that the level of depression is between moderate and severe, it was evidenced that psychological support in cancer patients is of great importance during medical treatment, mitigating the effects that the disease may entail, positively influencing the health of the patient.